Self Efficacy Perawat di Tengah Pandemi Covid-19 - Christianto Nugroho; Ikhwan Kosasih (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2022)
ABSTRACT Covid-19 is causing a global health crisis with the number of people being infected and dying every day. Seeing the number of cases and symptoms of Covid-19 patients illustrates that the number of patients and the risks that nurses must face, this affects the psychology of nurses in general and in particular affects the self-efficacy of nurses. The purpose of this study was to determine the self-efficacy of nurses amid the Covid-19 pandemic at the Kediri District Hospital. This research is a descriptive-analytic study with a quantitative approach at Pare Hospital in April– September 2021. The study population was all nurses at Pare Hospital with a total sample of 181 people using simple random sampling. Collecting data using self-efficacy questionnaire and univariate analysis. The results showed that 8(4.4%) respondents had low self-efficacy, 146(80.7%) moderate respondents, and 27(14.9%) good respondents. The conclusion of nurses' self-efficacy is mostly in the moderate category, so it needs support from all parties including hospital management to provide emotional support for existing health workers, so nurses will feel confident that they can treat and accompany Covid-19 patients properly and correctly. Keywords : Self Efficacy, Nurse, Covid-19.